Gangliocytic Paraganglioma of the Filum Terminale. A Rare Entity - Tavares, Sofia Isabel Carneiro Pereira Guerra; Costa, Gonçalo Maria Sengo Agante Guerreiro (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Paragangliomas are rare, benign and slow-growing neuroendocrine tumors that can arise from the adrenal medulla (85–90%) or from the extra-adrenal paraganglia.In the central nervous system (CNS), they can be found at several sites, but more often at the cauda equina and filum terminale region, where they account for between 2.5 and 3.8% of total tumor cases of that region. There are only 8 cases described in the literature that mention the presence of the gangliocytic variant of this entity at the filum terminale.We present the case of a 41-year-old man with chronic lumbar pain refractory to medical treatment, without any associated neurological deficits. Magnetic resonance imaging (MRI) revealed an intradural, extramedullar oval lesion with regular contours and homogeneous caption of contrast at L1 level.He was submitted to surgical treatment, with complete resection of the lesion. The histological analysis revealed a gangliocytic paraganglioma of the filum terminale. At 5 years of follow-up, he remains asymptomatic and without any signs of relapse.These are lesions with an overall good prognosis with gross total resection. Although the recurrence rate is extremely low, prolonged observation is recommended due to the slow-growing nature of the tumor, being estimated that between 1 and 4% can recur even after gross total removal.
Keywords: paraganglioma; gangliocytic; filum terminale; low back pain